Both flagella and F4 fimbriae from F4ac+ enterotoxigenic Escherichia coli contribute to attachment to IPEC-J2 cells in vitro - Zhou, Mingxu; Duan, Qiangde; Zhu, Xiaofang; Guo, Zhiyan; Li, Yinchau; Hardwidge, Philip R.; Zhu, Guoqiang (My University, 2013)
The role of flagella in the pathogenesis of F4ac[superscript +] Enterotoxigenic Escherichia coli (ETEC) mediated neonatal and post-weaning diarrhea (PWD) is not currently understood. We targeted the reference C83902 ETEC strain (O8:H19:F4ac[superscript +] LT[superscript +] STa[superscript +] STb[superscript +]), to construct isogenic mutants in the fliC (encoding the major flagellin protein), motA (encoding the flagella motor), and faeG (encoding the major subunit of F4 fimbriae) genes. Both the ΔfliC and ΔfaeG mutants had a reduced ability to adhere to porcine intestinal epithelial IPEC-J2 cells. F4 fimbriae expression was significantly down-regulated after deleting fliC, which revealed that co-regulation exists between flagella and F4 fimbriae. However, there was no difference in adhesion between the ΔmotA mutant and its parent strain. These data demonstrate that both flagella and F4 fimbriae are required for efficient F4ac[superscript +] ETEC adhesion in vitro.
Keywords: Escherichia coli; Neonatal pigs; Young pigs; Diarrhea